The Effect of Mass and Diameter of Waste Valves on the Efficiency of 3 inch Ram Hydraulic - Jafri, Muhamad; Sanusi, Arifin; Wangge, Gusti F.X. Wara (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
This study aim to analyze the effect of the mass and diameter of the waste valve on the efficiency of hydraulic pumps. This study method was an experiment on the specimens and analyzing the mathematical equations contained in the hydraulic pump theory. The data measured in this study were the flow of water in, discharge of wastewater, and discharge of water out. Independent variables in this study were the mass of the waste valve, namely 1.5 kg, 2.0 kg, 2.5 kg, 3.0 kg and the diameter of the waste valve was 2.0 inches, 2.25 inches, and 2.50 inches. While the dependent variable were the discharge and efficiency of the hydraulic pump. The results show that the mass of the waste valve and the diameter of the waste valve affected the efficiency of the hydraulic pump. The highest efficiency of the hydraulic pump occurred at a waste valve mass of 1.5 kg and a waste valve diameter of 2.5 inches which was 78.08%, and the lowest efficiency occurred at a mass of 3.0 kg waste valve and a 2.0-inch diameter of a waste valve which was 33. 56%.